Rheological behavior of carbon nanotubes/copper feedstocks for metal injection molding - ., Faiz Ahmad, Ali Samer Muhsan, M Rafi Raza (2012)
Metal injection molding (MIM) technology is known for its ability of producing near net shape components. This study presents the results of flow behavior of multi-walled carbon nanotubes (MWCNTs) reinforced copper composites mixes. The solid loadings in the copper mixes were investigated in the ranges of 55-61 V% using a binder. Copper mixes and copper/MWCNTs were compounded using a Z-blade mixer for homogenous dispersion of solids in the binder.